Nanometer-thick copper films with low resistivity grown on 2D material surfaces - Liu, Yu-Wei; Zhang, Dun-Jie; Tsai, Po-Cheng; Chiang, Chen-Tu; Tu, Wei-Chen; Lin, Shih-Yen (Scientific reports, 2022)
Thin Copper (Cu) films (15 nm) are deposited on different 2D material surfaces through e-beam deposition. With the assist of van der Waals epitaxy growth mode on 2D material surfaces, preferential planar growth is observed for Cu films on both MoS 2 and WSe 2 surfaces at room temperature, which will induce a polycrystalline and continuous Cu film formation. Relative low resistivity values 6.07 (MoS 2 ) and 6.66 (WSe 2 ) μΩ-cm are observed for the thin Cu films. At higher growth temperature 200 °C, Cu diffusion into the MoS 2 layers is observed while the non-sulfur 2D material WSe 2 can prevent Cu diffusion at the same growth temperature. By further increasing the deposition rates, a record-low resistivity value 4.62 μΩ-cm for thin Cu films is observed for the sample grown on the WSe 2 surface. The low resistivity values and the continuous Cu films suggest a good wettability of Cu films on 2D material surfaces. The thin body nature, the capability to prevent Cu diffusion and the unique van der Waals epitaxy growth mode of 2D materials will make non-sulfur 2D materials such as WSe 2 a promising candidate to replace the liner/barrier stack in interconnects with reducing linewidths.